2021
DOI: 10.3390/jpm11040251
|View full text |Cite
|
Sign up to set email alerts
|

Is Metformin a Possible Beneficial Treatment for Psoriasis? A Scoping Review

Abstract: Psoriasis is a chronic inflammatory condition with genetic, immunological, and metabolic etiology. The link between psoriasis and diabetes mellitus has been shown in genetic predisposition, environmental influences, inflammatory pathways, and insulin resistance, resulting in end-organ damage in both conditions. Because comorbidities often accompany psoriasis, the therapeutic management of the disease must also take into consideration the comorbidities. Given that metformin’s therapeutic role in psoriasis is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 77 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…In addition, a reduction in PASI score is achieved after 12 weeks of follow-up. Psoriasis refers to a long-term inflammation disorder associated with hyper proliferation and inflammation of the keratinocyte (15)(16)(17)(18). Such a multisystem chronic disease is usually associated with comorbidities such as obesity, diabetes, metabolic syndrome and arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a reduction in PASI score is achieved after 12 weeks of follow-up. Psoriasis refers to a long-term inflammation disorder associated with hyper proliferation and inflammation of the keratinocyte (15)(16)(17)(18). Such a multisystem chronic disease is usually associated with comorbidities such as obesity, diabetes, metabolic syndrome and arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…10,15 Also, oxidative stress is majorly involved in disease development. 16,[19][20][21] Metformin is used as a first-line antidiabetic medication in the treatment of diabetes mellitus (DM). It does not produce hypoglycemia; instead, it lowers serum glucose level by inhibiting hepatic glucose synthesis and improving peripheral tissue sensitivity to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding psoriasis, metformin showed improvement in PASI and some metabolic parameters [ 91 , 94 ]. Furthermore, in patients with diabetes, it could reduce the risk of developing psoriasis [ 94 ].…”
Section: Medications Used In the Prevention Of Atherosclerotic Cardio...mentioning
confidence: 99%
“…Regarding psoriasis, metformin showed improvement in PASI and some metabolic parameters [ 91 , 94 ]. Furthermore, in patients with diabetes, it could reduce the risk of developing psoriasis [ 94 ]. In a randomized controlled trial, an improvement in psoriasis was observed in metformin-treated patients compared to placebo [ 95 ].…”
Section: Medications Used In the Prevention Of Atherosclerotic Cardio...mentioning
confidence: 99%
See 1 more Smart Citation